Schinus terebinthifolius Leaf Lectin (SteLL) Reduces the Bacterial and Inflammatory Burden of Wounds Infected by Staphylococcus aureus Promoting Skin Repair - Marcio Anderson Sousa Nunes; Lucas dos Santos Silva; Deivid Martins Santos; Brenda da Silva Cutrim; Silvamara Leite Vieira; Izadora Souza Soeiro Silva; Simeone Júlio dos Santos Castelo Branco; Mayara de Santana do Nascimento; André Alvares Marques Vale; Ana Paula Silva dos Santos-Azevedo; Adrielle Zagmignan; Joicy Cortez de Sá Sousa; et al. (MDPI AG, 2022)
Staphylococcus aureus is commonly found in wound infections where this pathogen impairs skin repair. The lectin isolated from leaves of Schinus terebinthifolius (named SteLL) has antimicrobial and antivirulence action against S. aureus. This study evaluated the effects of topical administration of SteLL on mice wounds infected by S. aureus. Seventy-two C57/BL6 mice (6-8 weeks old) were allocated into four groups: (i) uninfected wounds; (ii) infected wounds, (iii) infected wounds treated with 32 µg/mL SteLL solution; (iv) infected wounds treated with 64 µg/mL SteLL solution. The excisional wounds (64 mm2) were induced on the dorsum and infected by S. aureus 432170 (4.0 × 106 CFU/wound). The daily treatment started 1-day post-infection (dpi). The topical application of both SteLL concentrations significantly accelerated the healing of S. aureus-infected wounds until the 7th dpi, when compared to untreated infected lesions (reductions of 1.95-4.55-fold and 1.79-2.90-fold for SteLL at 32 µg/mL and 64 µg/mL, respectively). The SteLL-based treatment also amended the severity of wound infection and reduced the bacterial load (12-fold to 72-fold for 32 µg/mL, and 14-fold to 282-fold for 64 µg/mL). SteLL-treated wounds show higher collagen deposition and restoration of skin structure than other groups. The bacterial load and the levels of inflammatory markers (IL-6, MCP-1, TNF-α, and VEGF) were also reduced by both SteLL concentrations. These results corroborate the reported anti-infective properties of SteLL, making this lectin a lead candidate for developing alternative agents for the treatment of S. aureus-infected skin lesions.